Maternal Obesity and Rectovaginal Group B Streptococcus Colonization at Term - Shelby M. Kleweis; Alison G. Cahill; Anthony O. Odibo; Methodius G. Tuuli (Hindawi Limited, 2015)
Objective. To test the hypothesis that maternal obesity is an independent risk factor for rectovaginal group B streptococcus (GBS) colonization at term. Study Design. Retrospective cohort study of consecutive women with singleton term pregnancies admitted in labor at Barnes-Jewish Hospital (2004-2008). Maternal BMI ≥ 30 Kg/m2 (obese) or <30 Kg/m2 (nonobese) defined the two comparison groups. The outcome of interest was GBS colonization from a positive culture. Baseline characteristics were compared using Student's t-test and Chi-squared or Fisher's exact test. The association between obesity and GBS colonization was assessed using univariable and multivariable analyses. Results. Of the 10,564 women eligible, 7,711 met inclusion criteria. The prevalence of GBS colonization in the entire cohort was relatively high (25.8%). Obese gravidas were significantly more likely to be colonized by GBS when compared with nonobese gravidas (28.4% versus 22.2%, P<0.001). Obese gravidas were still 35% more likely than nonobese women to test positive for GBS after adjusting for race, parity, smoking, and diabetes (adjusted OR 1.35 [95% CI 1.21-1.50]). Conclusion. Maternal obesity is a significant risk factor for GBS colonization at term. Further research is needed to evaluate the impact of this finding on risk-based management strategies.